Gender Differences in the Early Career Earnings of Economics Graduates - Stephen Bazen; Kadija Charni (Institute of Labor Economics (IZA), 2023)
In contrast to the UK, the USA and Germany, the majority of students in economics in France are female. Using a national survey of three cohorts of French university graduates in economics, we examine the gender differential in early career earnings. There is a significant raw differential in favour of male economics graduates in both starting pay and earnings three years after graduation, and the latter is wider than the former. Between 1998 and 2013 both gaps have narrowed but have not disappeared. The raw male-female pay differential stood at 10% for economics graduates in 2013. An Oaxaca decomposition reveals that nearly all of the gap is due to a persistent unexplained component. The gender differential among economics graduates is compared to that in two scientific subject areas: the female-dominated life sciences, and physics and chemistry (taken together) where a majority of graduates are male. The gender pay gap is smaller and the general level of earnings is lower in both science subject areas compared to economics. The decomposition attributes the limited gap in life sciences mainly to a composition effect, whereas in economics and physics and chemistry it is almost entirely due to the unexplained component. Gender differences in occupation suggest that female economics graduates are under-represented in more technical roles where two in five male graduates are found and where pay tends to be higher. However, even when occupation and sector are included as controls in an Oaxaca decomposition, two thirds of the gender differential remain unexplained.
Keywords: J31; J71; 330; gender earnings differentials; graduate labour market